On the discrepancies between macro and micro level identification of competitive strategies - Andrea M. Herrmann (Max Planck Institute for the Study of Societies, 2008)
As economic internationalization advances, the question of how firms cope with increasing pressure for competitiveness gains momentum. While scholars agree that firms need a competitive advantage, they debate whether firms exploit the comparative advantage of their economy and converge on that strategy facilitated by national institutions. No, argue strategic management proponents of the resource-based view. Yes, claim contributors to the competitiveness literature. My micro-level studies of these opposing views show that firms within one economy do not converge on the institutionally supported strategy. The discrepancies between these findings and the analyses of the competitiveness literature are attributed to differences in the indicators employed to measure corporate strategies. Whenever macro-level indicators are used, the related loss of information on micro-level variety entails that convergence effects are more pronounced possibly exaggerated.
Keywords: 300; Internationaler Wettbewerb; Wettbewerbsvorteil; Wettbewerbsstrategie; Pharmazeutische Industrie; Deutschland; Großbritannien; Italien